1H NMR-based metabolomics profiling and taste of boneless dry-cured hams during processing. (August 2019) - Zhang, Jian; Yi, Yue; Pan, Daodong; Zhou, Guanghong; Wang, Ying; Dang, Yali; He, Jun; Li, Gang; Cao, Jinxuan
Abstract: Boneless dry-cured hams were processed by raw material treatment (deboned and tumbled), salting (vacuum packed; 4 °C and 60–70% RH for 3.5 months), resting (vacuum packed; 15 °C and 60–70% RH for 1.5 months) and ripening (vacuum packed; 15 °C and 60–70% RH for 1.5 months). To explore the mechanisms that contributed to the taste of boneless dry-cured hams, 1 H NMR-based metabolomics combined with multivariate data analysis was applied to investigate metabolite changes during processing. A total of 28 metabolites, including amino acids, peptide, organic acids, nucleic acids and their derivatives, sugars and others were identified. PC1 and PC2 explained a total of 77.6% and 18.0% of variables, and thus they could well reflect the main characteristics of all samples. The contents of most metabolites had an upward trend during the processing. Amino acids (isoleucine, valine, alanine, glutamate and histidine), organic acids (lactate, acetate, succinate, citrate and formate) and nucleotide derivative (hypoxanthine) were the major contributors to the taste in our final product. We concluded that the processing time (within 6.5 months) had a positive effect on the development of taste of boneless dry-cured hams. Graphical abstract: Unlabelled Image Highlights: Metabolomics profiling and taste of boneless dry-cured hams during processing Amino acids and organic acids were the major contributors to the taste. Τhe processing time (within 6.5 months) had a positive effect on the taste. 1 H NMR was an effective tool to study the changes of metabolites during processing.